The real business of IT : how CIOs create and communicate business value - Hunter, Richard, 1952-; Westerman, George, 1963- (Boston, Mass. : Harvard Business Press, 2009)
The authors reveal that the cost mind-set, a real handicap to any business today, stems from IT leaders' inability to communicate about the business value they create, so CIOs get stuck discussing budgets rather than their contributions to the organization. Learn how to communicate effectively about value from IT investments.
Take the road to IT value -- Avoid the value traps -- Show value for money -- Master the virtuous cycle -- Find the sources of new value -- Assess and select IT investments transparently -- Integrate technology, business processes, and organizational change -- Measure the value delivered -- The CIO-plus -- There's never been a better time to be a CIO.
Includes bibliographical references and index.
Print version record.
Master record variable field(s) change: 082
Keywords: Information technology -- Management; Management information systems; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Technologie de l'information.; Investissements; Gestion d'entreprises.; Information technology -- Management; Management information systems; elektronické knihy; electronic books